Public Education and Growth in Developing Countries - Christiane Schuppert; Nadja Wirz (University of Copenhagen, Economic Policy Research Unit (EPRU), 2008)
Human capital plays a key role in fostering technology adoption, the major source of economic growth in developing countries. Consequently, enhancing the level of human capital should be a matter of public concern. The present paper studies public education incentives in an environment in which governments can invest in human capital to facilitate the adoption of new technologies invented abroad or, instead, focus on consumptive public spending. Although human capital is pivotal for growth, the model reveals that incentives to invest in public education vanish if a country is poorly endowed with human capital. Rather, governments of these poorly-endowed countries focus on consumptive public spending. As a result, while their better-endowed counterparts build up human capital thereby promoting technology adoption and growth, the growth process in poorly-endowed countries stagnates.
Keywords: O4; H4; F2; 330; growth; public education; human capital; technology adoption; Wirtschaftswachstum; Humankapital; Bildungsinvestition; Technischer Fortschritt; Innovationsdiffusion; Entwicklungsländer